Experimental investigation on the seismic performance of low-level corroded and retrofitted reinforced concrete bridge columns with CFRP fabric. (15th April 2020) - Jia, Junfeng; Zhao, Lingyun; Wu, Suiwen; Wang, Xu; Bai, Yulei; Wei, Yanjian
Highlights: Electrochemical method can result in non-uniform corrosion level among the rebars. Low level of corrosion in bridge column still results in flexural failure mode. Corrosion can cause substantial reduction in seismic capacity of bridge columns. CFRP fabric jacket can improve seismic behavior of corroded bridge columns. CFRP jackets could not improve the lateral strength of corroded columns. Abstract: Seismic damage mitigation of corroded reinforced concrete (RC) bridge columns in marine environment will be an impending problem in many countries in which a mass of bridges have been constructed for 20 or more years. In this paper, cyclic pseudo-static tests were conducted on three 1/4-scaled RC column specimens with and without retrofit by carbon fiber reinforced polymer (CFRP) fabric in order to investigate seismic performance of low-level corroded columns and the efficiency of CFRP as a retrofit measure. The first specimen was designed with normal design details of Chinese specifications, which worked as a reference. The second and third columns were both corroded with a target of low-level corrosion in the plastic hinge zone using an electrochemical method. Meanwhile, the third column was retrofitted by CFRP jackets in the plastic hinge region. The experimental results were then employed to evaluate the damage process, failure mode, displacement ductility, energy dissipation, lateral resistance strength, and residual displacement of each specimen. The results show that although low level of corrosion in the tested columns, the displacement ductility was significantly reduced due to weakened confinement of the corroded transverse rebars and reduced area of the corroded longitudinal bars. In addition, retrofitting the column using CFRP fabric jackets could significantly increase the displacement ductility and reduce the residual displacement to some extent. It is worth noting that retrofitting of corroded column using CFRP jackets did not improve the lateral strength.